Role of human Toll‐like receptors in naturally occurring influenza A infections. Issue 5 (1st April 2013) - Lee, Nelson; Wong, Chun Kwok; Hui, David S. C.; Lee, Sharon K. W.; Wong, Rity Y. K.; Ngai, Karry L. K.; Chan, Martin C. W.; Chu, Yi Jun; Ho, Amy W. Y.; Lui, Grace C. Y.; Wong, Bonnie C. K.; Wong, Sunny H.; et al.
<x xml:space="preserve">Abstract</x> Background We investigated the roles of Toll‐like receptors (TLRs) in naturally occurring influenza. Methods A prospective, case – control study was conducted. Adults hospitalized with virologically confirmed influenza A infections (onset <48 hours, before treatment) were compared with age‐/gender‐matched controls. TLRs (2, 3, 4, 7, 8, 9) expression in monocytes and dendritic cells (DCs – total, myeloid, plasmacytoid) was quantitated using flow cytometry. Gene expression of RLRs (RIG‐1, MDA‐5) was evaluated using real‐time PCR. Concomitant signaling molecules expression, plasma cytokine/chemokine concentrations, and respiratory tract viral loads were measured. PBMCs were cultured and stimulated ex vivo with TLR‐specific ligands for cytokine responses. Results Forty two patients with influenza (24 A/H3N2, 18 A/H1N1pdm09) and 20 controls were studied. Patients' mean age was 68 ± 16 years; 81% had respiratory/cardiovascular complications. There were increased cellular expressions of TLR9, TLR8, TLR3, and TLR7 during influenza; TLR2 and TLR4 were suppressed. Results were similar for both virus strains. Higher TLR expression levels at presentation significantly correlated with lower viral loads (Spearman's rho: −0·46 to −0·69 for TLR9, TLR8, and TLR3; P‐values <0·05). Multivariate regression models (adjusted for age, comorbidity, disease severity, time from onset) confirmed their independent associations. Increased signaling molecules (phospho‐MAPKs, IκB) and inflammatory cytokines (IL‐6, sTNFR‐1, CCL2/MCP‐1; CXCL10/IP‐10, IFN‐γ) correlated with increased TLR expression. RLRs were upregulated simultaneously. PBMCs of patients with influenza showed significant, dynamic changes in their cytokine responses upon TLR stimulation, compared with controls. Conclusions Our results suggest that TLRs play an important role in early, innate viral inhibition in naturally occurring influenza. Inflammatory cytokine responses are concomitantly induced. These findings support investigation of TLR targeting as a novel intervention approach for prophylaxis against influenza.